PERAN MAHASISWA KKN DALAM PEMBINAAN KARAKTER ANAK MELALUI KEGIATAN BELAJAR DI DESA NAGASARIBU I - Elisawati Hutabarat; Sriayu Sibarani; Corry Hanna Purba; Sanna Silalahi; Jalin Tarida Juanda Sitinjak; Eliakim Aliya; Yohan Esra Siburian; Melina Agustina Sipahutar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the role of Community Service Program (KKN) students in fostering children's character through learning activities in Nagasaribu I Village. This research employed a qualitative descriptive approach involving KKN students, children participating in tutoring programs, and community members as research subjects. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings revealed that KKN students played important roles as educators, facilitators, motivators, and role models in character development through literacy and numeracy (Calistung) tutoring and basic English learning programs. Learning activities were conducted using interactive and enjoyable methods, including educational games, discussions, question-and-answer sessions, and group exercises, which encouraged children's active participation. These programs not only improved children's reading, writing, arithmetic, and basic English vocabulary skills but also fostered positive character values, including discipline, responsibility, cooperation, self-confidence, social awareness, and learning motivation. The support of parents, village officials, and the local community also contributed significantly to the success of the programs. Therefore, KKN students made a meaningful contribution to improving both children's learning outcomes and character development in Nagasaribu I Village. Keywords: KKN Students, Character Development, Learning Activities, Literacy And Numeracy, Village Children.